Higher education and public and common good - Marginson, S (Centre for Global Higher Education, University of Oxford, 2024)
Higher education institutions generate multiple education, epistemic, economic, political, social and cultural outcomes but theory and policy lack satisfactory frameworks for defining, explaining, observing and regulating the full range of activity. In particular, in Anglophone jurisdictions, outcomes other than individual pecuniary benefits – both the broader formation of individual students, and the collective and relational outcomes for societies – are not well understood. The paper has been developed out of a comparative study of the non-pecuniary outcomes of higher education in ten countries. This non-pecuniary domain is variously understood using the English language terms ‘public good(s)’ and ‘common good(s)’, and their lexical equivalents in other languages. This paper does not focus on the comparative aspect, which is discussed elsewhere (e.g. Marginson & Yang, 2022). Rather it probes more deeply into the English language term ‘public’ and associated usages such as ‘public sector’, the ‘public good’, ‘public opinion’ and ‘public/private goods’. These terms are not universal but are grounded in Euro-American (Western) and specifically, Anglophone political culture.